THE INFLUENCE OF ISLAMIC EDUCATION TEACHERS’ LEADERSHIP ON STUDENTS’ DISCIPLINE AT MTs DARUL AITAM JEROWARU - Sirajul Januardi (Formad English Foundation NTB-Jakarta, 2024)
This study examines the influence of Islamic Education (PAI) teachers’ leadership on students’ discipline at MTs Darul Aitam Jerowaru. Education plays a crucial role in shaping individual behavior, with teachers serving as pivotal figures in fostering discipline and character development. Using a quantitative, descriptive correlational design, the research involved 28 students from Class 7A selected through purposive sampling. Data collection utilized a Likert-scale questionnaire to measure the relationship between PAI teachers’ leadership and students’ discipline, analyzed through descriptive and inferential statistical methods. The results indicate a significant positive relationship (r = 0.68) between the two variables. PAI teachers demonstrated leadership qualities such as consistency, firmness, and exemplary behavior, which positively impacted students' adherence to rules. Personalized approaches, discussions, and worship simulations emerged as effective strategies in promoting discipline and active student participation. These findings align with previous research emphasizing the importance of leadership in religious education for character development. The study suggests practical implications, including the need for teacher training programs to enhance leadership skills in classroom management, religious value integration, and effective communication. Theoretically, it highlights religious-based leadership as an effective approach for fostering discipline in Islamic education. However, limitations include a restricted sample size and reliance on subjective perceptions, suggesting future studies with broader scope and varied methodologies. These findings underscore the vital role of teacher leadership in nurturing disciplined and holistic student development.